Falsafah Pendidikan Islam dalam Syair Puji-Pujian Jawa Rukune Wong Urip - Robingun Suyud El Syam; Mukromin Mukromin (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2023)
This article aims to examine the philosophy of Islamic education in the Javanese hymn rukune wong urip, by focusing philosophical studies on the contemplation of the essence of Javanese society and then dissecting it regarding the focus of Islamic education, which has not been found specifically in previous research. Research is the result of findings from a qualitative type of literature research, with a philosophical approach to be able to draw conclusions through inductive analysis. The research concludes: that the Javanese hymn rukune wong urip is a philosophical embodiment of the nature of human being created by God in the world. Through deep contemplation to bring awareness to fulfill the obligations of a servant to his God. Implications for research to examine how the seven principles of awareness of life are more specific, further studies are needed. Research is expected to contribute to the philosophy of Islamic education.